Impact of cardiovascular risk factor control on long-term cardiovascular and all-cause mortality in the general population. (2nd October 2016) - Bérard, Emilie; Bongard, Vanina; Dallongeville, Jean; Arveiler, Dominique; Amouyel, Philippe; Wagner, Aline; Cottel, Dominique; Haas, Bernadette; Ruidavets, Jean-Bernard; Ferrières, Jean
Abstract: Purpose: In clinical trials, lowering cardiovascular risk factors (CVRFs) reduces cardiovascular (CV) morbidity and mortality. We assessed the impact of controlling CVRFs at baseline on long-term all-cause and CV mortality in the general population. Methods: Analysis was based on the Third French MONICA population-based survey (1994–1997). Vital status was obtained 18 years after inclusion. Statistical analysis was based on Cox-modelling. Results: About 3402 participants aged 35–64 were included and 569 (17%) presented with 2 or more uncontrolled CVRFs, 1194 (35%) had one uncontrolled CVRF, 770 (23%) had all CVRFs controlled under treatment (or were former smokers) and 869 (25%) exhibited no CVRF. During the follow-up, 389 deaths occurred (76 were due to CV causes). Considering all-cause mortality, the adjusted hazard ratios ( aHR ) for subjects with one uncontrolled CVRF and for those with two or more were 1.38 [1.03–1.83] (p = 0.029) and 1.80 [1.33–2.43](p < 0.001), respectively, as compared with subjects presenting with all their CVRFs controlled. For subjects exhibiting no CVRF, the aHR was 0.66 [0.44–0.98] (p = 0.042). Considering CV mortality, aHRs for subjects presenting with one and two or more uncontrolled CVRF were 1.70 [0.84–3.42] (p = 0.138) and 3.67 [1.85–7.29] (p < 0.001), respectively, as compared with subjects who had either all their CVRFs controlled or exhibited no CVRF. Conclusions: Failing to control CVRFs significantly increases long-term all-cause and CV mortality in the French general population. Key messages: Only 30% of patients with cardiovascular risk factors were controlled. Failing to control cardiovascular risk factors significantly increased long-term cardiovascular and all-cause mortality. A residual risk for all-cause mortality remained even when patients were controlled.